Analisis Interval Truck Concrete Pump dan Truck Mixer Terhadap Produktivitas Pengecoran Pierhead P37s Pada Proyek Jalan Tol Solo – Yogyakarta – Nyia Kulon Progo Seksi 2 Paket 2.1 A - Damara Risa Cahya Maulidya; M Bimo Bramantyo Aji; Fithri Estikhamah (Jurnal Teknik Sipil, 2026)
Pierhead casting is a critical activity in toll road infrastructure projects that requires continuous concrete supply to maintain quality and execution time. Factors influencing the smooth casting process include the regularity of truck mixer arrival intervals and the work cycle of the truck concrete pump. This study aims to analyze the effect of truck mixer intervals and truck concrete pump performance on the productivity of pierhead casting at Pierhead P37S on the Solo–Yogyakarta–NYIA Toll Road Project, Section 2 Package 2.1A. The analysis method used field observation through time study techniques to measure the cycle duration of truck mixers and the operating time of the truck concrete pump. The analysis stages included calculating cycle time, productivity, production capacity, and working duration of each equipment. The results show that the truck concrete pump achieved a productivity of 0.425 m³/minute, while the truck mixer reached 0.989 m³/minute. These values were influenced by cycle time, equipment condition, work area condition, execution method, and work volume. Based on duration analysis, the truck concrete pump required about 4.7 hours to complete the casting of 120 m³ of ready-mix concrete, while the truck mixer required 2.022 hours to support the concrete supply process.